Analisis Bibliometrik Perkembangan Penelitian Sistem Teknik pada Bidang Teknik Mesin Menggunakan VOSviewer dan Biblioshiny - Rezaabdulrahin Tanjung; Rafi Ahmad; Muhammad Rizky (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study aims to analyze the development of engineering system research in the field of mechanical engineering using a bibliometric approach. Data were collected from the Scopus database using the query TITLE-ABS-KEY ("engineering system" AND "mechanical engineering"), resulting in 1,000 articles published between 2023 and 2026. Biblioshiny and VOSviewer were employed to examine publication trends, subject area distribution, conceptual structure, author collaboration, author and source productivity, keyword evolution, thematic mapping, and international collaboration patterns. The findings reveal a significant increase in publication output, primarily dominated by Engineering, Materials Science, and Computer Science. Keyword analysis identifies failure (mechanical), safety engineering, machine learning, and forecasting as the major research themes. The results further indicate that the field has evolved through four major phases: Reliability-Based Engineering, Safety Engineering, Predictive Engineering Systems, and Intelligent Engineering Systems. Furthermore, this study proposes a conceptual evolution framework illustrating the transformation of engineering systems toward Autonomous Engineering Systems. The findings provide both theoretical and practical contributions by offering a comprehensive understanding of future research directions in AI-driven engineering systems.